Wykorzystanie modeli Holta-Wintersa w prognozowaniu brakujących danych - Zawadzki, Jan (Application of Holt-Winters Models in Forecasting of Missing Data, 2006)
The article presents exponential smoothing models in forecasting of economical variables with seasonal fluctuations in situation of lack of full information. The article proves that Holt-Winters models are useful in forecasting of times series with unsystematical gaps, which contained at least m observations at the beginning of the time series (m - length of cycle of periodical fluctuations). These observations are needed for estimate of output values of components for seasonality and trend. It attention was paid also to estimate "optimal" constant values of smoothing. Theoretical considerations in article were illustrated by empirical example.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 123-131